Risk factors for anxiety and depression among pregnant women during the COVID‐19 pandemic: Results of a web‐based multinational cross‐sectional study. Issue 1 (20th August 2022) - Kajdy, Anna; Sys, Dorota; Pokropek, Artur; Shaw, Steven W.; Chang, Tung‐Yao; Calda, Pavel; Acharya, Ganesh; Ben‐Zion, Maya; Biron‐Shental, Tal; Borowski, Dariusz; Czuba, Bartosz; Etchegaray, Adolfo; et al.
Abstract: Objective: To assess risk factors for anxiety and depression among pregnant women during the COVID‐19 pandemic using Mind‐COVID, a prospective cross‐sectional study that compares outcomes in middle‐income economies and high‐income economies. Methods: A total of 7102 pregnant women from 12 high‐income economies and nine middle‐income economies were included. The web‐based survey used two standardized instruments, General Anxiety Disorder‐7 (GAD‐7) and Patient Health Questionnaire–9 (PHQ‐9). Result: Pregnant women in high‐income economies reported higher PHQ‐9 (0.18 standard deviation [SD], P  < 0.001) and GAD‐7 (0.08 SD, P  = 0.005) scores than those living in middle‐income economies. Multivariate regression analysis showed that increasing PHQ‐9 and GAD‐7 scales were associated with mental health problems during pregnancy and the need for psychiatric treatment before pregnancy. PHQ‐9 was associated with a feeling of burden related to restrictions in social distancing, and access to leisure activities. GAD‐7 scores were associated with a pregnancy‐related complication, fear of adverse outcomes in children related to COVID‐19, and feeling of burden related to finances. Conclusions: According to this study, the imposed public health measures and hospital restrictions have left pregnant women more vulnerable during these difficult times. Adequate partner and family support during pregnancy and childbirth can be one of the most important protective factors against anxiety and depression, regardless of national economic status. Synopsis: Imposed public health measures and hospital‐level restrictions have made pregnant women more vulnerable to anxiety and depression during the COVID‐19 pandemic.